High cytokinin levels induce a hypersensitive-like response in tobacco - Novák, Jan; Pavlů, Jaroslav; Novák, Ondřej; Nožková-Hlaváčková, Vladimíra; Špundová, Martina; Hlavinka, Jan; Koukalová, Šárka; Skalák, Jan; Černý, Martin; Brzobohatý, Břetislav (Annals of botany, 2013)
BACKGROUND AND AIMS: Cytokinins are positive regulators of shoot development. However, it has previously been demonstrated that efficient activation of the cytokinin biosynthesis gene ipt can cause necrotic lesions and wilting in tobacco leaves. Some plant pathogens reportedly use their ability to produce cytokinins in disease development. In response to pathogen attacks, plants can trigger a hypersensitive response that rapidly kills cells near the infection site, depriving the pathogen of nutrients and preventing its spread. In this study, a diverse set of processes that link ipt activation to necrotic lesion formation were investigated in order to evaluate the potential of cytokinins as signals and/or mediators in plant defence against pathogens. METHODS: The binary pOp-ipt/LhGR system for dexamethasone-inducible ipt expression was used to increase endogenous cytokinin levels in transgenic tobacco. Changes in the levels of cytokinins and the stress hormones salicylic, jasmonic and abscisic acid following ipt activation were determined by ultra-performance liquid chromatography-electrospray tandem mass spectrometry (UPLC-MS/MS). Trends in hydrogen peroxide content and lipid peroxidation were monitored using the potassium iodide and malondialdehyde assays. The subcellular distribution of hydrogen peroxide was investigated using 3,3'-diaminobenzidine staining. The dynamics of transcripts related to photosynthesis and pathogen response were analysed by reverse transcription followed by quantitative PCR. The effects of cytokinins on photosynthesis were deciphered by analysing changes in chlorophyll fluorescence and leaf gas exchange. KEY RESULTS: Plants can produce sufficiently high levels of cytokinins to trigger fast cell death without any intervening chlorosis - a hallmark of the hypersensitive response. The results suggest that chloroplastic hydrogen peroxide orchestrates the molecular responses underpinning the hypersensitive-like response, including the inhibition of photosynthesis, elevated levels of stress hormones, oxidative membrane damage and stomatal closure. CONCLUSIONS: Necrotic lesion formation triggered by ipt activation closely resembles the hypersensitive response. Cytokinins may thus act as signals and/or mediators in plant defence against pathogen attack.
Keywords: buněčná smrt; Cytokinins; photosynthesis; cytokininy; hydrogen peroxide; chlorofyl; Gene Expression Regulation, Plant; Plants, Genetically Modified; lipid peroxidation; abscisic acid; Gene Silencing; non-photochemical quenching; Plant Leaves; Necrosis; peroxid vodíku; regulátory růstu rostlin; chloroplasty; Oxidative Stress; Lipid Peroxidation; fotosyntéza; Host-Pathogen Interactions; Cell Death; stomatal conductance; tabák; Nicotiana tabacum; umlčování genů; salicylic acid; Photosynthesis; geneticky modifikované rostliny; interakce hostitele a patogenu; dexamethason; regulace genové exprese u rostlin; Chlorophyll; Cytokinin; průduchy rostlin; alkyltransferasy a aryltransferasy; Plant Stomata; Alkyl and Aryl Transferases; nekróza; Dexamethasone; hypersensitive response; Plant Growth Regulators; oxidační stres; pathogenesis-related proteins; Nicotiana; jasmonic acid; Hydrogen Peroxide; listy rostlin; peroxidace lipidů; Chloroplasts